Implementasi Metode Triple Exponential Smoothing Untuk Prediksi Penjualan Alat Kesehatan - Ratih Yulia Hayuningtyas (Evolusi : Jurnal Sains dan Manajemen, 2020)
Easy Touch Kolestrol Strip is one of medical device sought after medical device by medical staff and pharmacies because it is very helpful in checking health. The large demand for these goods, so that the stock of goods becomes out of control and there is an increase in demand at certain times resulting in customer needs not fulfilled. The incraese in demand occurs because there is no estimated number of sales, so there is a need to review the number of sales. For this reason, a forecasting method is needed that can provide a forecast value of the number of goods sold in the following month. In this study, the Triple Exponential Smoothing method uses alpha constants from 0,1 to 0,5. The results of this test produce the smallest error value by looking at Mean Absolute Deviation, Mean Square Error, and Mean Absolute Percentage Error. The smallest error value obtained from the alpha constant value of 0,1 with a MAPE result of 0,33%.